2013
DOI: 10.1080/02640414.2013.770908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of target change during the simple attack in fencing

Abstract: The aim of this study was to test the effect that changing targets during a simple long lunge attack in fencing exerts on the temporal parameters of the reaction response, the execution speed, and the precision and the coordination of the movement pattern. Thirty fencers with more than 10 years of experience participated in this study. Two force platforms were used to record the horizontal components of the reaction forces and thereby to determine the beginning of the movement. A threedimensional (3D) system r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 18 publications
3
32
0
1
Order By: Relevance
“…Significantly, greater sword velocity in elite fencers has been attributed to more than arm extension velocity alone, with sword arm movement in coordination with the lower limb lunge distinguishing skilled from novice fencers (Yiou and Do 2000). Research has demonstrated that more skilled fencers coordinate timing of the lead kick out foot more effectively, with a delay between sword movement and foot movement (Gutiérrez-Dávila et al 2013), however this has not explained where additional propulsion, underpinning sword velocity, is generated. Rear knee range of motion and peak rear hip flexion have been identified as significant predictors of sword velocity (Bottoms et al 2013), however the relationship between the two has not been explored further.…”
Section: Methodsmentioning
confidence: 99%
“…Significantly, greater sword velocity in elite fencers has been attributed to more than arm extension velocity alone, with sword arm movement in coordination with the lower limb lunge distinguishing skilled from novice fencers (Yiou and Do 2000). Research has demonstrated that more skilled fencers coordinate timing of the lead kick out foot more effectively, with a delay between sword movement and foot movement (Gutiérrez-Dávila et al 2013), however this has not explained where additional propulsion, underpinning sword velocity, is generated. Rear knee range of motion and peak rear hip flexion have been identified as significant predictors of sword velocity (Bottoms et al 2013), however the relationship between the two has not been explored further.…”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have discussed the significance of the timing parameters of the reaction response time (RRT) in the fencer's efficiency [4,12,13]. They found that the relationship between the RRT and the kinematic parameters of a lunge depends on target change [15]. Also interesting is the observation that when the target changes, the temporal sequence of the movement pattern does not change appreciably [15].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the participants had already begun strike when the opponent started 35 presenting target and counter-strike stimuli at about 50ms. Additionally, the mean times (SDs) of the 36 opponent's counter-strikes (from his right heel rising from the floor to his sword reaching the 37 participants' head) were 168 (6.1) and 171 (9.8) ms for the expert and intermediate groups, 38 respectively. Also, there was no significant difference between the groups (t (14) = 1.74, p = .10, r 39 = .42).…”
mentioning
confidence: 99%